2013
DOI: 10.1038/nchem.1692
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated chemistry in the reaction between the hydroxyl radical and methanol at interstellar temperatures facilitated by tunnelling

Abstract: Understanding the abundances of molecules observed in dense interstellar clouds requires knowledge of the rates of gas phase reactions between two neutral species. However, reactions possessing an activation barrier were considered too slow to play any important role at the low temperatures in these clouds. Here we show that despite the presence of a barrier the rate coefficient for the reaction between the hydroxyl radical (OH) and methanol, one of the most abundant organic molecules in space, is almost two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
408
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 251 publications
(446 citation statements)
references
References 33 publications
33
408
2
3
Order By: Relevance
“…The rate coefficient for OH + propan-2-ol is also found to exhibit a notable inverse temperature dependence below 240 K, as shown in Figure 1(b), increasing by around an order of magnitude between 296 and 88 K. 5 The rate coefficients k OH + ethanol and k OH + propan-2-ol were measured over a range of total bath gas densities and, in contrast to the reaction of OH with methanol, 17 the measured rate coefficients demonstrate a pressure dependence at the low temperatures studied in this work, as shown in Figure 4. DISCUSSION Figure 5 shows the generic potential energy surface of the reaction of OH with ethanol or propan-2-ol, based on calculations reported in the literature, from which it can be seen that a weakly bound complex (between~18-27 kJmol -1 ) is formed prior to any barrier to abstraction.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The rate coefficient for OH + propan-2-ol is also found to exhibit a notable inverse temperature dependence below 240 K, as shown in Figure 1(b), increasing by around an order of magnitude between 296 and 88 K. 5 The rate coefficients k OH + ethanol and k OH + propan-2-ol were measured over a range of total bath gas densities and, in contrast to the reaction of OH with methanol, 17 the measured rate coefficients demonstrate a pressure dependence at the low temperatures studied in this work, as shown in Figure 4. DISCUSSION Figure 5 shows the generic potential energy surface of the reaction of OH with ethanol or propan-2-ol, based on calculations reported in the literature, from which it can be seen that a weakly bound complex (between~18-27 kJmol -1 ) is formed prior to any barrier to abstraction.…”
Section: Resultsmentioning
confidence: 95%
“…However, at low temperatures when the quantum mechanical tunneling mechanism dominates reaction, the product branching ratios are predominantly influenced by the shape of the vibrationally adiabatic reaction path, in other words, the barrier widths. 17,30,31 Therefore, in the case of OH + ethanol it is likely that hydrogen atom abstraction process is not occurring through the lowest energy barrier, which corresponds to abstraction from the CH 2 moiety (R2b) to form CH 3 CHOH, but instead through the barrier which has the largest imaginary frequency (~2300-2900 cm -1 ), which is abstraction from the hydroxyl group (R2c) resulting in ethoxy radical formation, CH 3 CH 2 O. [18][19][20] Although this channel has been experimentally and theoretically determined to be relatively inactive at ambient temperatures, 6,19 our previous work on the OH + methanol reaction has shown that abstraction via the barrier with the largest imaginary frequency (also the OH group, to form CH 3 O)…”
Section: E8mentioning
confidence: 99%
See 3 more Smart Citations